Burning up : losing our ozone layer - Greeley, August (New York : PowerKids Press, 2003)
Introduces what the ozone layer is, how it protects life on Earth, the damage done to it by CFCs, the danger of the increasingly large hole in the ozone layer, and what may be done to heal it.
Keeping earth safe -- Harmful chemicals -- The ozone hole -- Saving the ozone layer.
Includes bibliographical references (p. 23) and index.
4.2.
4.2
3-6
Keywords: Ozone layer depletion -- Juvenile literature; Ozone layer depletion; Ozone layer; Ozone layer; Ozone layer -- Environmental aspects